Die Stärkung grenzüberschreitender Kooperation „von unten” – Perspektiven für die Region SaarLorLux im gelebten Europa = Le renforcement de la coopération transfrontalière « par le bas » – Perspectives pour la région SaarLorLux dans l’Europe vécue - Dittel, Julia; Weber, Florian (2025)
Abstract: „Widespread cross-border activities and relations have moved European integration step by step from what was once the European periphery towards the centre. This Working Paper spotlights the SaarLorLux region and describes cross-border cooperation at grass-roots level, as realized in specific activities in 2024. Relevant data is derived from quantitative surveys at the communal (urban and rural district) level in Saarland, the département Moselle, and the Grand Duchy of Luxembourg, complemented by in-depth interviews with representatives of these bodies. The results show that decision makers at this level associate Europe closely with open borders, the common currency, and solidarity, and hence widely agree with the thesis that border regions are – despite all obstacles – laboratories of European integration. The sense of a joint borderland and of connection with Europe is correspondingly high, especially in districts directly on the border. The advantages of the border situation are real and present to those who live here, but the Covid pandemic has nevertheless left traces that have not yet been entirely erased. In this light, future cross-border cooperation calls for further positive input at the local level to fill the concept of Europe with life.“
Keywords: COVID-19; Gemeinde; Grenzüberschreitende Kooperation; Kommunalpolitik; Pandemie

Grenzüberschreitende Kooperationen zwischen Kommunen in der Großregion. Ein Praxisbericht aus Luxemburg - Gloden, Léon; Hengel, Max (Die Großregion SaarLorLux. Anspruch, Wirklichkeiten, Perspektiven, 2023)
Abstract: „Die kommunale und lokale Ebene spielen in der grenzüberschreitenden Zusammenarbeit eine Hauptrolle. Sie sind Motor in der wirtschaftlichen, sozialen und kulturellen Entwicklung sowie wichtige Akteure in der Mobilität. Nachstehend soll erläutert werden, inwiefern die kommunale Ebene als Motor der Großregion fungiert. Da die beiden Autoren exponierte Kommunalpolitiker in Gemeinden des Großherzogtums Luxemburg sind, die an Deutschland angrenzen, wird vornehmlich auf Praxisbeispiele der Zusammenarbeit zwischen Luxemburg und Deutschland rekurriert.“
Keywords: Gemeinde; Grenzüberschreitende Kooperation; Kommunalpolitik

Zwischen kommunaler Bevormundung und Autonomie. Paternalismus, Stagnation und basisdemokratisches Aufbegehren in Eupen-Malmedy - Kontny, Johannes (Staatenwechel, Identitätskonflikte, Kriegserfahrungen (1919–1945), 2018)
Keywords: Eupen-Malmedy; Gemeindeverwaltung; Kommunalpolitik